Environmental nanopollutants : sources, occurrence, analysis and fate - Szpunar, Joanna; Jiménez-Lamana, Javier (Royal Society of Chemistry, 2022)
Offering a wide overview of the most recent research on environmental nanopollutants this book gives the reader a full picture of the research on nanoparticles in the environment.
Keywords: Nanoparticles -- Environmental aspects.; Environmental chemistry.; Nanoparticules -- Aspect de l'environnement.; Chimie de l'environnement.; Environmental (see also Environmental Science); Environmental Conservation & Protection.; NATURE.; Nanotechnology & MEMS.; TECHNOLOGY & ENGINEERING.; Chemistry.; SCIENCE.; Environmental chemistry; Electronic books.